Validity and Practicality of Project-Based Learning Student Worksheets on The Subject of Environmental Pollution for Physics Phase E - Setivawani, Andrisa; Darvina, Yenni (PILLAR OF PHYSICS EDUCATION, 2025)
Teaching materials play a crucial role in the learning process and can greatly enhance the quality of education. An autonomous curriculum calls for better educational practices, and one such strategy is the Project Based Learning (PjBL) based Learner Worksheet (LKPD). The purpose of this research is to evaluate the efficacy and viability of a PBL-based LKPD on pollution in the environment lesson plan for physics class X. Using a development model modified from the 4D model, Research and Development (R&D) is the research kind employed. Three professors from FMIPA UNP's Physics department tested the efficacy of PjBL-based LKPD on environmental pollution content for upper-level physics courses. Over the course of the 2023–2024 academic year, 19 students from Fase E at SMA N 3 Bukittinggi, together with two physics instructors from that school and one from SMA N 2 Bukittinggi, participated in the practicality exam. Validity and practicality surveys were utilized as study instruments. The Aikens V formula was used to analyze the validity results, while descriptive statistics were employed to analyze the practicality results. The PJBL-based LKPD on environmental pollution for Physics phase E lessons met the legitimate criteria with an average score of 0.89846, according to the assessment analysis results from the three specialists: linguists, material experts, and media experts. With an average score of 88.286%, the PjBL-based LKPD on environmental pollution for Physics phase E learning fulfilled the practical criteria. This means that the material is valid, practical, and can be used for learning, according to the results of the practicality assessment sheet analysis, which involved 19 people from both the teaching and student populations.